Attending to Patients' Spirituality: An Evaluation of a Spiritual Screening Project from the Perspective of Nurses, Chaplains and Patients in a Belgian Hospital - Buelens, Eva (Counseling et spiritualité, 2016)
It is often found to be essential that nurses develop sensitivity to the spirituality of their patients, are able to give basic spiritual care and can make referrals to specialized spiritual caregivers (chaplains) when needed. At two wards in a Belgian hospital, we tested if the revised screening instrument SPIRIT would enhance the attention given to these elements. For six weeks, each newly admitted patient had a conversation with a nurse about four screening questions. Following this pilot test, we interviewed patients, nurses and chaplains. This article offers practice-based insights into several factors that facilitate or interfere in the use of the screening instrument and that might stimulate nurses to refer to a chaplain. Nurses are in need of time, emotional space, perceived competence, personal spirituality and a certain attitude towards the patients' life stance. A trusting nurse-patient relationship, willingness to talk about spirituality and the trust in and image of the chaplain also influence the way the screening is conducted and perceived. Interviewees listed the following advantages of the screening: integration of spiritual care, eye-opener to some patients, easier referral. However, the screening also has some drawbacks: artificial, time-consuming, possibly fewer referrals, probably triggers unnecessary emotions and the impossibility to screen every patient at any given time.